Design of an allosterically modulated doxycycline and doxorubicin drug-binding protein. - Schmidt, Karin; Gardill, Bernd; Kern, Alina; Kirchweger, Peter; Börsch, Michael; Muller, Yves (Proceedings of the National Academy of Sciences of the United States of America, 2018)
The allosteric interplay between distant functional sites present in a single protein provides for one of the most important regulatory mechanisms in biological systems. While the design of ligand-binding sites into proteins remains challenging, this holds even truer for the coupling of a newly engineered binding site to an allosteric mechanism that regulates the ligand affinity. Here it is shown how computational design algorithms enabled the introduction of doxycycline- and doxorubicin-binding sites into the serine proteinase inhibitor (serpin) family member α1-antichymotrypsin. Further engineering allowed exploitation of the proteinase-triggered serpin-typical S-to-R transition to modulate the ligand affinities. These design variants follow strategies observed in naturally occurring plasma globulins that allow for the targeted delivery of hormones in the blood. By analogy, we propose that the variants described in the present study could be further developed to allow for the delivery of the antibiotic doxycycline and the anticancer compound doxorubicin to tissues/locations that express specific proteinases, such as bacterial infection sites or tumor cells secreting matrix metalloproteinases.

NewBG: A surrogate corticosteroid-binding globulin with an unprecedentedly high ligand release efficacy - Gardill, Bernd; Schmidt, Karin; Muller, Yves (Journal of Structural Biology, 2019)
The introduction of ligand-binding sites into proteins and the engineering of molecular allosteric coupling pathways are topical issues in protein design. Here, we show that these issues can be addressed concurrently, using the serpin human α1-antichymotrypsin (ACT) as a model. We have introduced up to 15 amino acid substitutions into ACT, converting it into a surrogate corticosteroid-binding globulin (CBG), thereby creating a new binding globulin (NewBG). Human CBG and ACT share 46% sequence identity, and CBG served as the blue-print for our design, which was guided by side-chain-packing calculations, ITC measurements and crystal structure determinations. Upon transfer of ligand-interacting residues from CBG to ACT and mutation of specific second shell residues, a NewBG variant was obtained, which binds cortisol with 1.5 µM affinity. This novel serpin (NewBG-III) binds cortisol with a 33-fold lower affinity than CBG, but shares a similar ligand-binding profile and binding mode when probed with different steroid ligands and site-directed mutagenesis. An additional substitution, i.e. A349R, created NewBG-III-allo, which introduced an allosteric coupling between ligand binding and the serpin-like S-to-R transition in ACT. In NewBG-III-allo, the proteinase-triggered S-to-R transition leads to a greater than 200-fold reduction in ligand affinity, and crystal structures suggest that this is mediated by the L55V and A349R substitutions. This reduction significantly exceeds the 10-fold reduction in binding affinity observed in human CBG.
CRIS-Team Scopus Importer:2019-07-23
Keywords: Allostery; Computational protein design; Crystal structure; Ligand-binding site design; Serpin

PRISEs (progesterone 5β-reductase and/or iridoid synthase-like 1,4-enone reductases): Catalytic and substrate promiscuity allows for realization of multiple pathways in plant metabolism. - Schmidt, Karin; Petersen, Jan; Munkert, Jennifer; Egerer-Sieber, Claudia; Hornig, Michael; Muller, Yves; Kreis, Wolfgang (Phytochemistry, 2018)
PRISEs (progesterone 5β-reductase and/or iridoid synthase-like 1,4-enone reductases) are involved in cardenolide and iridoid biosynthesis. We here investigated a PRISE (rAtSt5βR) from Arabidopsis thaliana, a plant producing neither cardenolides nor iridoids. The structure of rAtSt5βR was elucidated with X-ray crystallography and compared to the known structures of PRISEs from Catharanthus roseus (rCrISY) and Digitalis lanata (rDlP5βR). The three enzymes show a high degree of sequence and structure conservation in the active site. Amino acids previously considered to allow discrimination between progesterone 5β-reductase and iridoid synthase were interchanged among rAtSt5βR, rCrISY and rDlP5βR applying site-directed mutagenesis. Structural homologous substitutions had different effects, and changes in progesterone 5β-reductase and iridoid synthase activity were not correlated in all cases. Our results help to explain fortuitous emergence of metabolic pathways and product accumulation. The fact that PRISEs are found ubiquitously in spermatophytes insinuates that PRISEs might have a more general function in plant metabolism such as, for example, the detoxification of reactive carbonyl species.